Sequência didática para o ensino de funções quadráticas usando atividades interativas da camada de computação do Desmos - SILVA, Jhonatan Oliveira da (2024)
This essay presents educational strategies through a didactic sequence in the Desmos com putational layer aimed at teaching and learning quadratic functions, in order to make the teaching of this content more attractive and thus reflect positively on this learning process. Interactive activities already created in Desmos are explored, as well as other authorial ac tivities to explore the elements of quadratic functions, graphical properties, maximum and minimum problems and application in physics; thus promoting more diversified teaching with the contemporary demands of the digital age.